Pengaruh Kebermanfaatan, Kemudahan, Dan Sikap Terhadap Penggunaan Aplikasi DANA Pada Generasi Millenial Di Sukoharjo - Milani Milani; Ghegana Ariel Sheda; Wahyu Septia Wulandari; Nanda Nur Latifah; Fitriyatul Sakinah; Ambar Usnul Fatimah; Novia Mayasari (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This study aims to analyze the effect of convenience, benefits, and attitudes on the use of the DANA application. The population of this study is the millennial generation of DANA application users in Sukoharjo. The number of samples used was 154 respondents. The data testing method used is validity test, reliability test, classic assumption test, F test, T test. Data calculation uses SPSS version 23 software. The research method used is quantitative and the theory used is the Technology Acceptance Model (TAM) with 4 variables namely the variable Benefit, Convenience, Attitude and usage. The results of this study obtained variables that did not have a significant effect, namely the variable convenience. Meanwhile, the variables of utility and attitude have a significant effect on the variable use of the DANA application for the millennial generation in Sukoharjo.